PEMBINAAN KEDISIPLINAN SISWA DI SMA NEGERI 8 BANJARMASIN - Nur Ramadhania (JURNAL SOCIUS, 2014)
School is one of the places that used to guide, educate, direct, and forman individual person to behave well. School also has contribution in introducing, cultivating, nurturing, and enhancing the value of disciplined to learners, including to the compliance of the school’s rules. This research used qualitative descriptive method and implemented at SMA Negeri 8 Banjarmasin. As informants in this study were the Principal, Vice Principal of Students’ Affairs, Sub Vice Principal of Students’ Affairs, counseling guidance teacher, and teachers of school subjects. Data collection techniques used were observation, interview, and documentation. Coaching which is conducted on students at SMAN 8 Banjarmasin looked pretty good seen from the application of discipline that uses Points System. As the result, the application of the Points System was poorly socialized to the students and their parents/guardians. The school also facilitate the students to follow the organizational activities such as OSIS (Intra-School Students Organization), as well as the activities of self-development through extracurricular activities. In addition, every teacher in the school also implemented discipline during the teaching and learning process. The Points System which has been applied by the school is very precise to construct discipline to their students.  Keywords: Coaching, Discipline